Enhanced Performance of Ternary CuGaSe2 Thin‐Film Photovoltaic Solar Cells and Photoelectrochemical Water Splitting Hydrogen Evolution with Modified p–n Heterointerfaces (Adv. Mater. Interfaces 25/2022). Issue 25 (2nd September 2022) - Ishizuka, Shogo; Okamoto, Riku; Ikeda, Shigeru
Abstract : Efficient Photovoltaic Solar Cell and Hydrogen Evolution Using CuGaSe2 ‐based Photoabsorber Layers In article number 2201266, Shogo Ishizuka, Riku Okamoto, Shigeru Ikeda, and co‐workers develop an interface modification technique using Cu‐deficient phases, alkali‐metal doping, and an n‐type buffer material for enhancing performance of CuGaSe2 thin‐film photovoltaic solar cells and photoelectrochemical water splitting hydrogen evolution.